Dairy Cattle Response to a Virtual Fence When Pasture on Offer Is Restricted to the Post-grazing Residual - Colusso, Patricia I.; Clark, Cameron E. F.; Ingram, Lachlan J.; Thomson, Peter C.; Lomax, Sabrina (Frontiers in Animal Science, 2021)
Pasture-based dairy systems rely on the accurate allocation of pasture to both meet livestock requirements and maintain the growth of herbage. Currently, physical fences are used to contain livestock however they can be labour-intensive to shift and maintain. Alternatively, virtual fence (VF) systems offer flexibility and real-time control of livestock location. Pre-commercial neckbands (eShepherd®, Agersens, Melbourne, VIC) emit a warning audio tone (AT) when a cow approaches a VF boundary, paired with an electrical pulse (EP) if the cow continues forward into the exclusion zone. However, the ability of VF technology to control animal location when pasture is restricted to the previous day’s residual, remains unknown. Ten non-lactating Holstein-Friesian dairy cows were trained to use a VF system for six days before strip grazing a 1.2 ha paddock of annual ryegrass. Over 10 days the cows grazed eight pasture allocations at a pre-grazing pasture mass of 2,324 ± 81 kg DM/ha (mean ± SE) and post-grazing pasture-mass (post-grazing residual) of 1,649 ± 48 kg/DM/ha with a front VF. The allocations had a physical backing fence that included the fresh allocation and a small area of residual to cater for any GPS drift of the front VF. On each day, with the exception of days 5 and 10, the VF was moved forward, and the cows were provided a new pasture allocation. On days 5 and 10, the VF was not shifted, and cows were only offered the previous allocation’s residual pasture. The location of each animal (inclusion, buffer and exclusion zones) and number of stimuli (AT and EP) delivered were recorded. The number of stimuli delivered between the grazing and hold-off days was similar. Cows spent 89% of time within the inclusion zone, with significant peaks observed on day 5 and 10. Distance that cows travelled into the exclusion zone reduced across time. There was also evidence of individual variation in the number of stimuli and thus time spent in each zone. Overall, the VF system was successful in containing the dairy cows during strip grazing even when only offered the previous days post-grazing residual.